2020
DOI: 10.1080/09637486.2020.1722075
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to DASH dietary pattern is inversely associated with osteoarthritis in Americans

Abstract: Osteoarthritis (OA) is one of the most common diseases that cause disability among older adults. The objective of this study was to assess the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) and OA in American adults. This study included adults ( aged 20 years) who participated in the National Health and Examination Survey (NHANES) 2007-2016 in the United States. Adherence to the DASH score was calculated from 8 food groups. Higher scores indicate better adherence to the DAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Esta pesquisa mostra que indivíduos que apresentam comorbidades consomem significativamente menos alimentos considerados protetores, o que confirma resultados de outros estudos que analisaram associação do consumo alimentar e DCNT (NGUYEN et al, 2016;PIRODDI et al, 2017;PETERSON et al, 2018;COMEE et al, 2019;ZHANG et al, 2020). Esses são fatores reconhecidamente de risco para DCNT, onde a alimentação equilibrada é determinante para saúde do indivíduo que busca um estilo de vida saudável.…”
Section: Discussionunclassified
“…Esta pesquisa mostra que indivíduos que apresentam comorbidades consomem significativamente menos alimentos considerados protetores, o que confirma resultados de outros estudos que analisaram associação do consumo alimentar e DCNT (NGUYEN et al, 2016;PIRODDI et al, 2017;PETERSON et al, 2018;COMEE et al, 2019;ZHANG et al, 2020). Esses são fatores reconhecidamente de risco para DCNT, onde a alimentação equilibrada é determinante para saúde do indivíduo que busca um estilo de vida saudável.…”
Section: Discussionunclassified
“…In contrast, a diet high in trans and saturated diets is negatively linked with this malady (Dyer et al, 2016). tests used as parameters for OA (Park, 2019;Vina & Kwoh, 2018;Zhang et al, 2020). Other researchers have found that vitamin K has a strong association with hand and knee OA.…”
Section: Dietmentioning
confidence: 99%
“…Knee OA is sturdy associated with a diet low in vitamin C and vitamin D. Previous studies show a weak bond between vitamin D and OA. But recent research found strong evidence that individuals with sufficient levels of vitamin D3/25‐hydroxyvitamin D are at lower risk of OA than those who have low levels as damage to cartilage, physical function ability, cartilage volume, synovitis effusion tests used as parameters for OA (Park, 2019; Vina & Kwoh, 2018; Zhang et al, 2020). Other researchers have found that vitamin K has a strong association with hand and knee OA.…”
Section: Lifestyle Factors Influencing Oa Progressionmentioning
confidence: 99%
“…Another study found that individuals with OA believed that what they eat could impact their health ( 36 ). The majority of existing survey-based research investigating nutrition and OA is epidemiological, with a focus on examining roles of specific nutrients and dietary patterns on OA symptoms and progression ( 24 , 25 , 37 , 38 ). Moreover, dietary changes made by people with OA are typically done without consulting an HCP or specialist ( 36 ).…”
Section: Introductionmentioning
confidence: 99%